Tumor Angiogenesis Therapy Using Targeted Delivery of Paclitaxel to the Vasculature of Breast Cancer Metastases. (7th December 2014) - Zhu, Shijun; Kisiel, Walter; Lu, Yang J.; Petersen, Lars C.; Ndungu, John M.; Moore, Terry W.; Parker, Ernest T.; Sun, Aiming; Liotta, Dennis C.; El-Rayes, Bassel F.; Brat, Daniel J.; Snyder, James P.; et al.
Abstract : Breast cancer aberrantly expresses tissue factor (TF) in cancer tissues and cancer vascular endothelial cells (VECs). TF plays a central role in cancer angiogenesis, growth, and metastasis and, as such, is a target for therapy and drug delivery. TF is the cognate receptor of factor VIIa (fVIIa). We have coupled PTX (paclitaxel, also named Taxol) with a tripeptide, phenylalanine-phenylalanine-arginine chloromethyl ketone (FFRck) and conjugated it with fVIIa. The key aim of the work is to evaluate the antiangiogenic effects of PTX-FFRck-fVIIa against a PTX-resistant breast cancer cell line. Matrigel mixed with VEGF and MDA-231 was injected subcutaneously into the flank of athymic nude mice. Animals were treated by tail vein injection of the PTX-FFRck-fVIIa conjugate, unconjugated PTX, or PBS. The PTX-FFRck-fVIIa conjugate significantly reduces microvessel density in matrigel (p < 0.01 – 0.05 ) compared to PBS and unconjugated PTX. The breast cancer lung metastasis model in athymic nude mice was developed by intravenous injection of MDA-231 cells expressing luciferase. Animals were similarly treated intravenously with the PTX-FFRck-fVIIa conjugate or PBS. The conjugate significantly inhibits lung metastasis as compared to the control, highlighting its potential to antagonize angiogenesis in metastatic carcinoma. In conclusion, PTX conjugated to fVIIa is a promising therapeutic approach for improving selective drug delivery and inhibiting angiogenesis.